InGaAs tunnel FET with sub-nanometer EOT and sub-60 mV/dec sub-threshold swing at room temperature - Alian, A.; Mols, Y.; Bordallo, C. C.M.; Verreck, D.; Verhulst, A.; Vandooren, A.; Rooyackers, R.; Agopian, P. G.D. [UNESP]; Martino, J. A.; Thean, A.; Lin, D.; Mocuta, D.; et al. (AIP Publishing, 2016)
InGaAs homojunction Tunnel FET devices are demonstrated with sub-60 mV/dec Sub-threshold Swing (SS) measured in DC. A 54 mV/dec SS is achieved at 100 pA/μm over a drain voltage range of 0.2-0.5 V. The SS remains sub-60 mV/dec over 1.5 orders of magnitude of current at room temperature. Trap-Assisted Tunneling (TAT) is found to be negligible in the device evidenced by low temperature dependence of the transfer characteristics. Equivalent Oxide Thickness (EOT) is found to play the major role in achieving sub-60 mV/dec performance. The EOT of the demonstrated devices is 0.8 nm.